Study guides

Q: 6a plus 7b - 4a - 8b equals?

Write your answer...

Submit

Related questions

11a+7b-(3b-2a)

6a+7b

9a + 7b *remember to look and understand the letters!*

(6a + 7b)(6a - 7b)

Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?

6a+7b. This cannot be simplified anymore unless you know a or b.

2a+2a-7b+7b =4a

It is 20a - 5b - 9.

The given expression can be simplified to: 3b-a

-58

It is an equation and the value of b is 3

3b -2 =7 b+4

It is: 19b+7b = 26b

7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4

If: 6b+21 = 7b-21 Then: 6b-7b = -21-21 And: -b = -42 So: b = 42

(-a-7b+5)4ab

It is: 7b+10 simplified

If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.

-7 7b + 15 = (-34) 7b = (-34) - 15 7b =(-49) b = (-49) / 7 b= (-7)

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7

8b

It is: 7b+4b-1b = 10b when simplified

4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.

5 - 7b + 6 = -24 is a linear equation in one variable. 11 - 7b = -24 Adding -11 to both sides 11 - 7b + (-11) = -24 + (-11) 11 - 7b - 11 = -24 - 11 -7b = -35 Dividing both sides by -7 -7b/(-7) = -35/(-7) b = 5

For him he is doing fine.